Analyst coverage and the cost of raising equity capital: Evidence from underpricing of seasoned equity offerings - BOWEN, Robert M. (Institutional Knowledge at Singapore Management University, 2008)
Theorists have long recognized that information asymmetry among investors adversely affects the cost of raising equity capital (e.g., Diamond and Verrecchia 1991). When there is information asymmetry, relatively uninformed investors are reluctant to trade because of higher potential loss from transacting with informed investors (e.g., Glosten and Milgrom 1985; Kyle 1985). To trade, uninformed investors demand compensation for the risks of trading with informed investors (O’Hara 2003). In the case of issuing new equity, firms must issue shares at a discount to overcome the reluctance of uninformed investors. Such discounting leads to smaller proceeds to the firm and a higher cost of raising equity capital.Firms can reduce information asymmetry among investors through public disclosures or information intermediaries. Information asymmetry here refers broadly to differences in information sets among investors, including both differences in knowledge about the firm and the possibility that certain investors are not aware of the firm. In Merton’s 1987 words, it refers to both the depth and breadth of investor cognizance. Although a large body of research investigates the impact of public disclosures on the cost of capital, there is limited direct evidence on the impact of information intermediaries. Given that financial analysts occupy a central role in the acquisition and dissemination of information in capital markets, we investigate whether the amount and nature of analyst coverage are associated with the cost of raising equity capital.